Struktur kepemilikan, arus kas operasi, tingkat hutang dan volatilitas penjualan sebagai faktor penentu persistensi laba - Mulya, Anissa Amalia; Andini, Prita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
It is important for investors to estimate the financial performance of the companies they invest in, with earnings sustainability as a key indicator. This study aims to explore the relationship between ownership structure, operating cash flow, debt level, and sales volatility and earnings sustainability in food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange for the period 2020–2022. Using the purposive sampling method, 30 companies were selected as research samples. Data analysis was carried out through multiple linear regression using SPSS software. The results showed that operating cash flow significantly contributed to earnings sustainability. However, ownership structure, debt level, and sales volatility have no significant impact on earnings sustainability. The findings provide important insights for investors in planning their investments, highlighting the importance of paying attention to factors that affect corporate earnings sustainability in making investment decisions.